2019
DOI: 10.4103/ijri.ijri_441_18
|View full text |Cite
|
Sign up to set email alerts
|

Role of apparent diffusion coefficient as a biomarker in the evaluation of cervical cancer

Abstract: Background: Diffusion-weighted magnetic resonance imaging (DW-MRI) has evolved as a major diagnostic and prognostic tool in cervical cancer. The aim of our study was to compare the change in mean apparent diffusion coefficient (ADC) value before and after concurrent chemoradiation therapy (CCRT) in carcinoma cervix thereby establishing its role as a cancer biomarker. Materials and Methods: A hospital-based prospective study was conducted in 35 patients diagnosed with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Despite mixed results as to whether lower ADC values portend a better or worse prognosis, [23,33] the literature in recent years has generally supported an association between higher ADC values and better outcomes. [24,25,31,32,[34][35][36] Our results are in line with this nding. Figure 3A illustrates an important bimodal distribution: while lower 90th percentile ADC values are spread between the CMR and non-CMR groups, the cohort of patients with high 90th percentile ADC values ( ≥ ~ 2.5 x 10 − 3 mm 2 /s) almost universally achieved a CMR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite mixed results as to whether lower ADC values portend a better or worse prognosis, [23,33] the literature in recent years has generally supported an association between higher ADC values and better outcomes. [24,25,31,32,[34][35][36] Our results are in line with this nding. Figure 3A illustrates an important bimodal distribution: while lower 90th percentile ADC values are spread between the CMR and non-CMR groups, the cohort of patients with high 90th percentile ADC values ( ≥ ~ 2.5 x 10 − 3 mm 2 /s) almost universally achieved a CMR.…”
Section: Discussionsupporting
confidence: 91%
“…1D, Patient B, black arrow in the ADC map), portending a favorable response to ISBT. [34] Despite consensus on the direction of this association, agreement has not yet been reached as to ADC cutoff values that could be used to risk-stratify cervical cancer patients. Ho, et al found a 90th percentile pretreatment ADC cutoff value of 1.917 x 10 − 3 mm 2 /s, with lower values associated with worsened outcomes, [25] while our data suggests a 90th percentile ADC cutoff value of 2.10 x 10 − 3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
“…Members of this team produced one of the earliest studies that evaluated DWI as a biomarker of early response in cervical cancer ( Harry et al, 2008 ). Since then, DWI has been increasingly explored in the prediction and early assessment of treatment response in cervical carcinomas ( Chen et al, 2010 , Dashottar et al, 2019 , Hameeduddin and Sahdev, 2015 , Kuang et al, 2014 , Lee et al, 2014 , McVeigh et al, 2008 , Yang et al, 2018 , Zheng et al, 2020 ). Using the DW images, ADC maps have been generated and allow for the quantification of ADC before and during treatment, potentially offering a more individualized approach in treating these patients while reducing unnecessary toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors with internal necrosis or cystic areas with higher ADC values indicate more hypoxic tumor tissue and are less responsive to chemoradiation. Tumors with low pretreatment ADC values are more responsive to chemoradiation [ 29 ]. Additionally, DWI is also helpful for determining tumor response to chemoradiation in cervical cancer when morphological changes are not apparent on other sequences, as tumors show an increase in ADC value from baseline.…”
Section: Clinical Applications In Gynecological Malignanciesmentioning
confidence: 99%